PELAKSANAAN PELAYANAN PUBLIK DAN KEPUASAN MASYARAKAT DI KECAMATAN KOTA WAINGAPU, KABUPATEN SUMBA TIMUR - dena, novianus (Jurnal Ilmiah Dinamika Sosial, 2018)
ABSTRACTFormulation of the problem of this research is how the implementation of public service and the satisfaction of the people in the management of e-ID card in the district town Waingapu. The purpose of research is to determine the public service and community satisfaction in the management of e-ID card in the district town Waingapu. The technique of collecting data using questionnaires and observation. Data were analyzed using quantitative data analysis techniques supported by questionnaire. The results of the study can be said that the public service and the satisfaction of the people in the management of e-ID card in the district town Waingapu eastern Sumba has been going well.Keywords: Public Service, Local Community, Public Policy